Power Management Problem for Civil Aircraft under More Electric Environment. (24th January 2020) - Yang, Yuanchao; Gao, Zichen
Abstract : The civil aviation industry is moving toward the more electric aircraft (MEA) which is to use electrical power to meet the load demands on multiple aircraft subsystems which are conventionally driven by other power resources. Thus, there will be introduced a large amount of new electrical power demands which are safety-critical for aircraft's flight and this may lead the challenge for a reliable and efficient power management problem (PMP): the balance between the aircraft power supply and demands while minimizing the operation costs. To cope with the PMP for civil aircraft under more electric environment, in this paper, we explicitly give a detailed and complete modeling of all power supply resources (fuel and battery) and safety-critical electrical loads and cast the PMP as a mixed-integer nonlinear programming problem; we develop a practical solution methodology for the application on the real civil MEA. The proposed formulation and solution algorithm can give an efficient power schedule result with the minimal fuel and battery operation cost through a smart codispatch between the gas turbine generator, storage devices, and all electrical loads of MEA. Numerical testing results based on one real civil aircraft case demonstrate the economic and operational effectiveness.